The British Payments and Exchange Control System - Shannon, H. A. (Quarterly Journal of Economics, 1949)
I. Bretton Woods and convertibility, 212. — II. The Exchange Control Act of 1947, 214. — III. Sterling balances, 216. — IV. Sterling area agreements, 218. — V. The American Account, Transferable Account and Bilateral areas; and their relative importance, 222. — VI. Payments agreements with the Transferable Account area, 226. — VII. And with the Bilateral area, 230. — VIII. "Administrative Transferability, " 233. — IX. The intra-European payments agreement and American aid, 234.